Arti Penting Mullā Ṣadrā dan Karatristik Aliran Pemikirannya - Syaifan Nur (Al-Jami'ah: Journal of Islamic Studies, 1996)
This article is intended to introduce Mullā Ṣadrā and his thought to Indonesian readers. Born and brought up in the Shi'i religious tradition. Mullā Ṣadrā has been known as one of the greatest Persian thinkers. Especially in metaphysics. In spite of the fact, the position of Mullā Ṣadrā and the significance of his thought have hardly been known outside Persia (Iran). In his attempt to find a truth. Mullā Ṣadrā used three approaches, i.e., by synthesizing and harmonizing revelation. Illumination and reason. In addition to these methods, he also reconciled various schools of Islamic Thought which had existed befor such as masysyā'ī (periparetic), isyrāqi (illumination). ‘irfānī (Gnosticism or sufism). And kalām (Islamic theology). In formulating his ideas. Mullā Ṣadrā employed Qur'ān verses. Prophetic tradition 'Sunnah), opinions of Shi’I Imāms, as well as his deep individual thinking and reflections. The way Mullā Ṣadrā formulated his ideas has made him a great thinker who could create a grand thesis called al-ḥikmat al-muta’aliyah. Mullā Ṣadrā grand thesis is very different from other thinkers, thesis such as al-ḥikmat al-masysyāī‎ah or al-ḥikmat al-Isyrāqīyah. So far, Mullā Ṣadrā’s influence has been confined to shií countries, chiefly Iran where his works and ideas have been broadly and profoundly studied from generation to generation. Based on this fact, the writer argues that it is groundless to say that Islamic philosophy in the Muslim world become stagnant after the demise of the great philosophers like ibn rushed were never produced in the sunnī Muslim countries. In Contrast to the writer, intellectual discourses and philosophical life in a shi’I Muslim Country like Iran has never stopped but always developed from time to time. The writer argues that Sunni Muslim scholar should pay attention to Islamic Studies in Iran, and Sunnis Negative views of shiísm should be wiped out.